Effective Length Factors for Gusset Plate Buckling - Dowswell, Bo (Engineering Journal, 2006)
Gusset plates are commonly used in steel buildings to connect bracing members to other structural members in the lateral force resisting system. Failure modes for gusset plates have been identified, and design procedures are well documented in the literature, but uncertainties still exist for gusset plates in compression. The previous research includes laboratory tests, finite element models, and theoretical studies. Many of the previous studies concentrated on the capacity of gusset plates in compression. A literature review revealed a total of 170 experimental specimens and finite element models with compressive loads applied. The procedures that are currently used to design gusset plates are reviewed. Using the experimental and finite element data from the previous studies, the capacity of gusset plates in compression are compared to the current design procedures. Based on a statistical analysis, effective length factors are proposed for use with the current design procedures.